Gelatin nanofiber assisted zero order release of Amphotericin-B: A study with realistic drug loading for oral formulation. (September 2020) - Gaydhane, Mrunalini; Choubey, Pankaj; Sharma, Chandra S.; Majumdar, Saptarshi
Graphical abstract: Highlights: Nanofibrous oral tablets of Amphotericin B for the potential cure of Leishmaniasis are synthesized. A realistic drug dose (60 mg AmB) is maintained. Crosslinking, compressing and coating strategies are combined to control the release kinetics. Zero order release is achieved till 4 days while the tablet degrades on 5th day. Mechanism of drug release viz. drug diffusion and polymer degradation is established. Abstract: Oral administration of Amphotericin B (AmB) is abstained due to its poor bioavailability and high toxicity. Current intravenous lipid formulations are delivered as 3−5 mg AmB/kg of body weight, due to its dose dependent nephrotoxicity. In this work, we engineer the electrospun gelatin nanofibers to enable their use for controlled release of AmB in the form of oral tablets while focusing on loading realistic drug doses of AmB as per the clinical guidelines for the treatment of Visceral Leishmaniasis. A detailed study is carried out to understand the effect of different crosslinking strategies, drug concentrations, compressive loading (to form tablets) and additional protective layer of sodium alginate on release kinetics. Based on the outcome of these studies, we developed a systematic protocol to achieve the controlled release and minimizing the frequency of dosing in order to attain less toxicity at realistic body pH condition. The swelling and enzymatic degradation studies further infer the realistic stability of the tablet and its correlation with the in-vitro release kinetics of drug.